Supervised Mathematics curricular internship in the contexto of the Covid-19 pandemic - Rejane Waiandt Schuwartz de Carvalho Faria; Caroline Mendes dos Passos; Aline Marçal Rossinol; Luciano Gonçalves Batista (Pesquisa e Ensino, 2021)
With a qualitative methodological approach, this article aims to expose the experiences lived during the realization of two disciplines of Supervised Mathematics Internship in the remote modality, under the perspective of the trainees and supervising teachers. After highlighting the scenario of adaptations imposed by the SARS-coV2 virus, especially in the educational field, the reports of two interns, students of the Mathematics Degree course and two teachers who guided the internship disciplines in this new context are presented. Errors and successes were exposed, registering a new moment in the academic trajectory of the authors. However, it is worth noting that the work developed in collaboration was the major contribution, showing that everyone involved in an educational process, students of Basic Education, trainees, teachers, principals, pedagogical coordinators, parents and family, can get out of this process strengthened, equipped with new tools, in search of an education in which the subjects involved play a participatory role.